Legalitas Tindakan Aborsi (Abortus) Akibat Perkosaan Incest Ditinjau dari Hukum Pidana Adat di Wilayah Masyarakat Adat Kabupaten Timor Tengah Selatan - Khusnul Khusy Pit’ay; Aksi Sinurat; Debi F. Ng. Fallo (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The Timorese tribe has a pamali or prohibition not to be related or marry the same clan in one tribe or blood relations for people who are related by blood will be subject to customary sanctions by the traditional chief. The case of incest rape occurred in Nuapin Village, Fatumnasi District, South Central Timor Regency, this rape resulted in the victim experiencing an unwanted pregnancy by the victim and her family because the victim was pregnant with a child from her blood family which is prohibited in Timorese customary law, so she chose to have an abortion. Law No. 36 of 2009 concerning health and its Implementing Regulations excludes the act of abortion due to rape even though it is prohibited in the Criminal Code. In this case, the act of abortion is carried out as a result of incest rape and will be reviewed based on customary criminal law. The type of research used in this study is empirical research with a sociological juridical approach, namely field research whose object is about events and phenomena that occur in society. Data collection was carried out with two events, namely interviews with 4 people and literature studies. The data obtained were then presented in a qualitative descriptive manner. The results of this study show that: (1) The existence of criminal law prohibits the legalization of abortion due to incest rape, abortion is only allowed in emergency medical conditions in accordance with Law Number 36 of 2009 and Government Regulation Number 61 of 2014. (2). The legality of customary criminal law for abortion due to incest is carried out in Nuapin Village because it is considered to violate customary and pamali law.